Unjuk kerja reaktor alir tangki berpengaduk - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT Stirred tank flow reactor is commonly used in the chemical industry. Reactor performaiice will influence systems in the chemical industry. Reactor performance prediction can be evaluated by the residence time distribution from stimulus response experiment with a tracer. Stirred tank flow reactor used was completed by baffles. Hydrochloric acid was used as a tracer and water as fluid flow. Variables investigated in this experiment were residence time distribution, stirred speed and ratio of impeler diameter to reactor diameter. Reactor performance was expressed in the axial dispersion model as well as number of tank in series model. The effect of variables investigated to reactor performance can be expressed in the following equation: